Supervision on Social Media: Use and Perception of Facebook as a Research Education Tool in Disadvantaged Areas - Pimmer, Christoph; Chipps, Jennifer; Brysiewicz, Petra; Walters, Fiona; Linxen, Sebastian; Gröhbiel, Urs (International Review of Research in Open and Distributed Learning, 2016)
This exploratory study investigates how a typically disadvantaged user group of older, female learners from rural, low-tech settings used and perceived a Facebook group as a research supervision and distance learning tool over time. The within-stage mixed-model research was carried out in a module of a part-time, advanced midwifery education course in rural South Africa. To address the research questions, three quantitative and qualitative surveys were repeated, pre, post, and three months post evaluation. The findings indicate that using the social media space lowered learners' threshold to accessing educational resources. The increased ease of communication was afforded in particular by using mobile phones to access the space. The analysis also suggests that the social networking site became a more integral part of students' learning environments. The learners' use of the site to discuss further course and work-related issues increased during the intervention and also remained significantly higher in the three-month, post evaluation survey, indicating the routinisation and habitualisation of this learning space. The practical implications and constraints of using social networking spaces to enhance disadvantaged groups of learners’ access to educational resources are discussed.